(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
Technological development of foreign represent, a cultural breaching for our society, whose effects have crystallized in cultural and economic globalization, which forming a major challenge to the loss of identity and non-affiliation to Culture of origin, because the technology is tool and the way of development, so any progress should depend on it. The risks lies in not understanding the mechanism of dealing with this technology for all segments of society, especially young people. The understanding is to take advantage of its positive aspects and employ them to serve our development, such as manufacturing technology, communications, medical engineering, space, information technology. Within the framework of sustainable development, which creates the conditions for their own permanence and continuity, and make us not dependent on the West with is technology as well as caution from its negative effects which is the misuse of this technology, begin its misuse has a destructive effects on the values of youth and ethics and thinking and social and mental life in general. Also in the industrialization of all types and take it as a gift ready. Without processing the keys of this technology, to crystallize it to serve our society and without the need for the West in creating and continuing its continuity and development according to our needs. As well as the lack of awareness of the danger of the targets of the West from the dissemination and commercialization of this technology in our society which represents in the opening of our country markets for the disposal of manufactured products at the expenses of our national industries. The dissemination of a culture of consumption in our society and the cultural management of emerging generation through the invasion of space channels. And the communication technology that is being handled incorrectly and that will lead. As a result, to the productive work values that lead to making our country a source of raw materials that serve the manufacture of the West and further development at the expense of our development. In the face of this challenge. Intellectual and social currents have emerged to confront institutions, social organizations, and in all sectors. They should have been studied and take care of it in order to develop appropriate solutions, thus avoiding their effects and employing positive aspects to serve our development issues. تمثل التطورات التكنولوجية غريبة المنشأ اختراقاً ثقافياً لمجتمعنا تبلورت اثاره في العولمة الثقافية والاقتصادية، مشكلاً تحدياُ كبيراً يهدد بفقدان الهوية واللاإنتماء لثقافة الأصل. لأن التكنولوجيا أداة وطريق التنمية أساساً ولا بد للسير في طريق التقدم من الاخذ بها، تكمن المخاطر بعدم فهم آلية التعاطي الصحيح معها بالنسبة لكل شرائح المجتمع وخاصة الشباب، الفهم الذي يكمن في الاستفادة من جوانبها الإيجابية وتوظيفها لخدمة تنميتنا، كـ تكنولوجيا التصنيع – الاتصالات – الهندسة الطبية – الفضاء – تقنيات المعلوماتية وذلك في إطار التنمية المستدامة التي تخلق شروط دوامها واستمرارها بنفسها، وتجعلنا غير مرتهنين للغرب فيما لديه من تكنولوجيا، وكذلك الحذر من آثارها السلبية، والتي تتمثل في الاستخدام الخاطئ لهذه التكنولوجيا، وما لاستخدامها الخاطئ من آثار مدمرة على قيم الشباب والأخلاق والتفكير والحياة الاجتماعية والعقلية بشكل عام. كذلك على صعيد التصنيع بأنواعه وأخذه كمعطى جاهز، دون امتلاك مفاتيح هذه التكنولوجيا، لبلورتها بما يخدم مجتمعنا وبأيدينا دون الحاجة الى الغرب في خلقها ودوام استمرارها وتطويرها حسب حاجاتنا. كذلك عدم الوعي لخطر أهداف الغرب من نشر وتسويق هذه التكنولوجيا في مجتمعنا والمتمثلة في فتح بلادنا أسواقاً لتصريف منتجات تصنيعه على حساب صناعاتنا الوطنية، ونشر ثقافة الاستهلاك في مجتمعنا والتدمير الثقافي للأجيال الصاعدة في الغزو المتمثل بالأقنية الفضائية وتكنولوجيا الاتصالات التي يجري التعامل معها بطريقة غير صحيحة، والانصراف نتيجة ذلك عن قيم العمل المنتج الذي يقود الى جعل بلادنا مصدراً للمواد الأولية الخام التي تخدم تصنيع الغرب وزيادة تطوره على حساب تنميتنا وتطورنا. أمام هذا التحدي الذي لا مفر منه ظهرت تيارات فكرية واجتماعية لمواجهته – مؤسسات – منظمات اجتماعية، ولدى كافة الفعاليات. وكان لابد من دراستها والاهتمام بها لوضع الحلول المناسبة، وبالتالي تفادي آثارها السلبية وتوظيف الجوانب الإيجابية فيها لخدمة قضايا التنمية لدينا.